Occurrence of entomopathogenic nematodes in Golaghat District of Assam - Devi, Gitanjali; George, Jisna; Saikia, Mitali (International Journal of Environment, Agriculture and Biotechnology, 2019)
A survey of entomopathogenic nematodes was conducted in different vegetations of Golaghat district of Assam. Soil samples were tested for the presence of steinernematid and heterorhabditid nematodes by baiting with Galleria mellonella larvae. Out of 100 soil samples studied only one was positive for entomopathogenic nematodes (1%), containing one Steinernema isolate. Morphological and morphometrical studies were undertaken to characterize the isolate. The Steinernema isolate was identified as S. kushidai.